2020
DOI: 10.1002/er.5740
|View full text |Cite
|
Sign up to set email alerts
|

Graphene oxide coated nanosheet‐like γ‐MnS @ KB‐S fabricated by spray drying for high energy density Li‐S batteries

Abstract: In order to prohibit the shuttle influence of lithium polysulfides in lithium sulfur battery, a kind of graphene oxide (GO) coated γ-MnS@KB-S (GO@MKB-S) composite cathode material was successfully fabricated. First of all, the γ-MnS@KB (MKB) composite powders were prepared via a solvothermal reaction, then a spray drying method was used to obtain GO@MKB-S composites, which displays core/shell nanostructure. SEM, TEM, XRD as well as Raman spectrum are implemented to look into the microstructures and the functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 53 publications
(94 reference statements)
0
2
0
Order By: Relevance
“…Recently, targeted research has focused on introducing sulfur into microporous structure, which facilitates the immobilization of small sulfur molecules (S 2‐4 ) and confining polysulfides by the limited pore size 40‐45 . Interestingly, the storage of S 2‐4 in micropores is able to avoid the unnecessary conversion between S 8 to S 6 2− and S 4 2− , efficaciously improving active material utilization and alleviating the “shuttle effect” 46‐48 . Therefore, it is urgent to take measures to utilize the micropores of MOFs to confine and immobilize S and polysulfides, thereby increasing the sulfur utilization 49,50 …”
Section: Introductionmentioning
confidence: 99%
“…Recently, targeted research has focused on introducing sulfur into microporous structure, which facilitates the immobilization of small sulfur molecules (S 2‐4 ) and confining polysulfides by the limited pore size 40‐45 . Interestingly, the storage of S 2‐4 in micropores is able to avoid the unnecessary conversion between S 8 to S 6 2− and S 4 2− , efficaciously improving active material utilization and alleviating the “shuttle effect” 46‐48 . Therefore, it is urgent to take measures to utilize the micropores of MOFs to confine and immobilize S and polysulfides, thereby increasing the sulfur utilization 49,50 …”
Section: Introductionmentioning
confidence: 99%
“…Carbon materials, such as conductive carbon black, graphene, and carbon nanotubes (CNTs), which improve the electronic conductivity during the charge/discharge process, were introduced for Li–S batteries . Guo et al reported a graphene oxide-coated γ-MnS@KB composite material via a solvothermal method. The synthesized electrode displays excellent electrochemical performance due to the high conductivity of carbon materials.…”
Section: Introductionmentioning
confidence: 99%